2019
DOI: 10.1038/s41380-018-0313-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of up to 622,409 individuals identifies 40 novel smoking behaviour associated genetic loci

Abstract: Smoking is a major heritable and modifiable risk factor for many diseases, including cancer, common respiratory disorders and cardiovascular diseases. Fourteen genetic loci have previously been associated with smoking behaviour-related traits. We tested up to 235,116 single nucleotide variants (SNVs) on the exome-array for association with smoking initiation, cigarettes per day, pack-years, and smoking cessation in a fixed effects meta-analysis of up to 61 studies (up to 346,813 participants). In a subset of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 73 publications
8
94
0
3
Order By: Relevance
“…Beyond our discovery of rs1862416 with ND, SNPs across the TENM2 gene have been identified at genome-wide significance, as presented in the GWAS catalog 57 , for educational attainment, 38 smoking initiation (ever vs. never smoking), 5,[58][59][60] age of smoking initiation, 5 smoking cessation (current vs. former smoking), 5 cigarette pack-years, 61 alcohol consumption (drinks per week), 5 lung function, 60,62 height, 60 number of sexual partners, 58 depression, 63,64 risk taking tendency, 58 body mass index, 60 menarche (age at onset) 65 , and regular attendance at a religious group 66 . Our pairwise comparisons supported pleiotropic associations in the TENM2 region.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond our discovery of rs1862416 with ND, SNPs across the TENM2 gene have been identified at genome-wide significance, as presented in the GWAS catalog 57 , for educational attainment, 38 smoking initiation (ever vs. never smoking), 5,[58][59][60] age of smoking initiation, 5 smoking cessation (current vs. former smoking), 5 cigarette pack-years, 61 alcohol consumption (drinks per week), 5 lung function, 60,62 height, 60 number of sexual partners, 58 depression, 63,64 risk taking tendency, 58 body mass index, 60 menarche (age at onset) 65 , and regular attendance at a religious group 66 . Our pairwise comparisons supported pleiotropic associations in the TENM2 region.…”
Section: Discussionmentioning
confidence: 99%
“…We have also contributed to multiple other meta-analyses of GWAS data on various smoking and alcohol phenotypes, notably the GSCAN consortium GWAS and exome analyses (Brazel et al, 2018;Erzurumluoglu et al, 2019;Liu et al, 2019), for nicotine dependence (Hancock et al, 2018) and alcohol dependence (Walters et al, 2018). These analyses have been based on alcohol and smoking behavior data from the surveys, as well as from the structured psychiatric interviews conducted as part of the NAG study.…”
Section: Genetics and Epigenetics Of Smoking Nicotine Metabolism Andmentioning
confidence: 99%
“…igarette smoking has an estimated heritability of 40-70% 1,2 , and is a leading cause of morbidity and mortality worldwide. In the past two decades, over 25 genome-wide association studies (GWAS) of smoking and smoking-related phenotypes have been reported [3][4][5][6][7][8][9] . Among several hundred reported loci, the established loci are predominantly in a few genomic regions, such as 15q25 (CHRNA5-A3-B4) and 8p11 (CHRNB3-CHRNA6) 3,4,10,11 .…”
mentioning
confidence: 99%